Bioinformatic Analysis of the Proteome in Exosomes Derived From Plasma: Exosomes Involved in Cholesterol Metabolism Process of Patients With Spinal Cord Injury in the Acute Phase - Wu, Chunshuai; Yu, Jinjuan; Xu, Guanhua; Gao, Hong; Sun, Yue; Huang, Jiayi; Sun, Li; Zhang, Xu; Cui, Zhiming (Frontiers in Neuroinformatics, 2021)
Spinal cord injury(SCI) is a common but severe disease caused by traffic accidents. Coronary atherosclerotic heart disease（CHD） caused by dyslipidemia is known as the leading cause of death in patients with SCI. However, our quantitative analysis showed that the cholesterol and lipoprotein concentrations in peripheral blood did not change significantly within 48 hours after SCI. Due to the presence of the Blood spinal cord barrier(BSCB), there is only few studies concerning about the plasma cholesterol metabolism in acute phase of SCI. Exosomes have smaller particle size, which enable them relatively less limitation of BSCB. This study uses exosomes derived from plasma of 43 patients in acute phase of SCI and 71 patients in control group as samples. MS proteomics and bioinformatics analysis found 590 quantifiable proteins, in which 75 proteins were up-regulated and 153 proteins were down-regulated, and the top10 differentially expressed proteins are those including downregulating proteins: HIST1H4A, HIST2H3A, HIST2H2BE, HCLS1, S100A9, HIST1H2BM, S100A8, CALM3, YWHAH, and SFN, and upregulating proteins: SERPIND1, C1QB, SPTLC3, IGHV4-28, C4A, IGHV4-38-2, IGHV4-30-2, SLC15A1, C4B, and ACTG2. Enrichment analysis showed that the largest part proteins were related to cholesterol metabolism among the down-regulated proteins. The main components of cholesterol (ApoB-48 and ApoB-100 increased, ApoA-I, ApoA-II, ApoA-IV, ApoC, ApoE and Apo(a) decreased) were changed in exosomes derived from plasma of patients. Elisa analysis showed that some components were disordered in the acute phase of SCI. These results suggested that the exosomes might be involved in cholesterol metabolism regulation in the acute phase of SCI.